2010
DOI: 10.3732/ajb.1000073
|View full text |Cite
|
Sign up to set email alerts
|

Induction of programmed cell death in Arabidopsis and rice by single‐wall carbon nanotubes

Abstract: Consequently, SWCNTs have an adverse effect on protoplasts and leaves through oxidative stress, leading to a certain amount of programmed cell death. Although nanomaterials have great advantages in many respects, the benefits and side effects still need to be assessed carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(122 citation statements)
references
References 42 publications
(62 reference statements)
4
109
0
Order By: Relevance
“…Arabidopsis thaliana wild-type (Columbia) and acd5 mutant plants (Greenberg et al, 2000) were grown on soil under fluorescent lights as described by Shen et al (2010). The double mutants acd5 loh2 and acd5 loh3 were generated by crossing acd5 with loh2 (SALK_018608) or loh3 (SALK_150849), respectively, and isolated from the F2 progeny by PCR genotyping for T-DNA insertion in loh2 or loh3 and sequencing for the point mutation in acd5 (Supplemental Table 1).…”
Section: Plants and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis thaliana wild-type (Columbia) and acd5 mutant plants (Greenberg et al, 2000) were grown on soil under fluorescent lights as described by Shen et al (2010). The double mutants acd5 loh2 and acd5 loh3 were generated by crossing acd5 with loh2 (SALK_018608) or loh3 (SALK_150849), respectively, and isolated from the F2 progeny by PCR genotyping for T-DNA insertion in loh2 or loh3 and sequencing for the point mutation in acd5 (Supplemental Table 1).…”
Section: Plants and Materialsmentioning
confidence: 99%
“…For chemical treatments, protoplasts were made according to the procedure of Shen et al (2010). The viability was determined by fluorescein diacetate staining (Liang et al, 2003).…”
Section: Protoplast Isolation and Treatmentsmentioning
confidence: 99%
“…MWCNTs (10 mg/L) decreased cell dry weight, viability, chlorophyll content and superoxide dismutase (SOD) activity of Arabidopsis thaliana cell suspension [93]. SWCNTs had adverse effects on protoplasts and leaves through oxidative stress, leading to a certain amount of programmed cell death in Arabidopsis thaliana [110].…”
Section: Fate and Impacts Of Carbon Nanotubes On Plantsmentioning
confidence: 99%
“…[110] Thale cress (Arabidopsis thaliana ecotype Columbia Col-0) 10; 20 and 50 mg/L CNT characterisation: TEM / The three types of CNTs were directly taken up and translocated to roots, stems and leaves functionalisation of CNTs induced strong treatments which are reducing the CNT length. It is thus difficult to determine if functionnalisation or CNT matters most for the toxicity.…”
Section: Fate and Impacts Of Carbon Nanotubes On Plantsmentioning
confidence: 99%
“…On the other hand, studies have shown that carbon-based nanoparticles such as single walled carbon nanotubes triggered reactive oxygen species (ROS) generation in Arabidopsis and rice (Oryza sativa) (Shen et al, 2010). In addition, multiwall carbon nanotubes have been found to induce gene expression of heat shock protein (HSP) 90 in tomato leaves and roots (Khodakovskaya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%